1994
DOI: 10.1161/01.atv.14.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat induces changes in factor VII coagulant activity through effects on plasma free stearic acid concentration.

Abstract: Previous studies have demonstrated activation of the contact system of coagulation and an increase in factor VII coagulant activity (VIIc) when citrated plasma is incubated in the presence of micellar stearate. The products of contact activation, factors Xlla and IXa, were responsible in this system for the activation of factor VII, thereby increasing factor VIIc. To obtain evidence that these in vitro interactions also operate in vivo, factor VIIc was examined in relation to plasma free fatty acid concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 42 publications
1
57
1
3
Order By: Relevance
“…40 In addition, fat intake influences NEFA concentrations and factor VII activity. 41 Although NEFAs represent the main energy source for the resting heart, high NEFA concentrations also predispose to arrhythmia. 42,43 Paolisso et al 44 recently showed in patients with type 2 diabetes that a high basal plasma NEFA concentration was associated with a high frequency of ventricular premature complexes and that increased NEFA concentration (by intralipid infusion) increases ventricular premature complexes whereas decreased NEFA concentration (by acipimox administration) decreases them.…”
Section: Carlsson Et Al Nonesterified Fatty Acids and Familial Cvdmentioning
confidence: 99%
“…40 In addition, fat intake influences NEFA concentrations and factor VII activity. 41 Although NEFAs represent the main energy source for the resting heart, high NEFA concentrations also predispose to arrhythmia. 42,43 Paolisso et al 44 recently showed in patients with type 2 diabetes that a high basal plasma NEFA concentration was associated with a high frequency of ventricular premature complexes and that increased NEFA concentration (by intralipid infusion) increases ventricular premature complexes whereas decreased NEFA concentration (by acipimox administration) decreases them.…”
Section: Carlsson Et Al Nonesterified Fatty Acids and Familial Cvdmentioning
confidence: 99%
“…Tholstrup et al [8] reported a favourable effect of a diet high in stearic acid vs. diets rich in other short-chain SFAs (lauric, myristic and palmitic); however, in this study there was a pronounced reduction of plasma cholesterol after a stearic-rich diet and the effect on FVII c of the change of this interrelated variable, as well as the plasma concentration of FAs, were not evaluated. On the other hand, Mitropoulos et al [7] reported a substantial increase of FVII c after a highsaturated fat diet. Moreover, in this study the plasma concentration of stearic acid, which increased significantly after the high-saturated fat diet, was strongly associated with FVII c .…”
Section: Discussionmentioning
confidence: 97%
“…A methodological aspect should be taken into account when a comparison between our study and that of Mitropoulos et al [7] presence of tissue thromboplastin and calcium ions [26]. Very recently (after the beginning of our study) a sensitive method for measuring directly the two-chain activated form of FVII (FVII a ) has become available [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, small FVIIc differences (2%) between fats rich in either palmitic (palm oil) or myristic acid (synthetic fat) were found (Tholstrup et al, 1994b). Finally, one study reported that a SFA-rich high-fat diet is associated with higher FVIIc, FVIIag, and FVIIa levels than a n-6 PUFA-rich high-fat diet (Mitropoulos et al, 1994). We would suggest that the low number of participants (®ve) and limited dietary control of this study might have led to the con¯icting ®nding by chance.…”
Section: Diet and Fasting Fviimentioning
confidence: 96%